1979
DOI: 10.2337/diab.28.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Morphology and Function in Isolated Islets of the Zucker Rat

Abstract: Obesity in the Zucker rat is accompanied by hyperlipemia, hyperinsulinism, insulin resistance, pancreatic hyperplasia, and islet hypertrophy. This study correlates the morphologic heterogeneity of isolated pancreatic islets with secretion of insulin and glucagon in the perifusion system. Islet size was arbitrarily defined as large (greater than 0.45 mm) or small (smaller than 0.12 mm). Protein content and volume (V = 4/3pir3) were calculated for groups and individual islets, respectively. Islets from obese rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 15 publications
3
24
1
Order By: Relevance
“…Similar morphological changes in the islets have been observed in male Zucker fatty rats (23), which also show a decreased response of A cells to hypoglyceÂŹ mia (24). As reported previously (10), exercise training prevented morphological alterations of the islets of OLETF rats of 24 weeks old, such as enlargement and lobulation of islets due to proliferation of connective tissue.…”
Section: Discussionsupporting
confidence: 71%
“…Similar morphological changes in the islets have been observed in male Zucker fatty rats (23), which also show a decreased response of A cells to hypoglyceÂŹ mia (24). As reported previously (10), exercise training prevented morphological alterations of the islets of OLETF rats of 24 weeks old, such as enlargement and lobulation of islets due to proliferation of connective tissue.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, it appears that moderate exercise training improves beta cell function either directly by increasing beta cell mass or as a result of bsparingQ insulin needs by increasing peripheral insulin action. Indeed, a strong positive correlation exists between the maintenance of normal islet morphology and beta cell function [50]. Our immunohistochemical analysis of the pancreas showed that in exercised animals there was a significant attenuation in the reduction of beta cell mass when compared with age-matched controls (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously shown that when groups of islets from obese and lean rats are perifused, the observed pattern of insulin release in response to stimulation is closely correlated to islet size (Hayek and Woodside 1979). Perifusion of groups of islets however, obscures the synchrony of insulin secretion in discreet short pulses exhibited by individual, normal islets (Beigelman, Thomas, Slavin, Shu and Bessman 1973).…”
Section: Resultsmentioning
confidence: 96%
“…Individual large islets (0.4 to 0.8 mm diameter) from obese rats were perifused in Hanks' solution adjusted to a pH of 7.4 and gassed continuously with 95 % 0 2 and 5 % C0 2 (Hayek and Woodside 1979).Flow rate, maintained at 1 ml/min, allowed the collection of 250 ”l aliquots every 15 seconds. Aliquots were immediately frozen and simultaneously assayed at a later time for insulin by radioimmunoassay.…”
Section: Methodsmentioning
confidence: 99%